Higher, Faster, Better: Maternal Effects Shorten Time Lags and Increase Morphological Defenses in Daphnia lumholtzi Offspring Generations - Graeve, Annette; Janßen, Marjan; Villalba de la Pena, Mariana; Tollrian, Ralph; Weiss, Linda C. (Frontiers in Ecology and Evolution, 2021)
Prey species can respond to the presence of predators by inducing phenotypic plastic traits which form morphological, life history or behavioral defenses. These so-called inducible defenses have evolved within a cost-benefit framework. They are only formed when they are needed, and costs associated with defenses are saved when predators are not present. However, a disadvantage compared to permanent defenses are lag phases between predator perception and the full formation of defenses. This may be especially important when the predation risk persists for longer periods, e.g., outlasts one generation and challenges prey offspring. We hypothesized that transgenerational induced phenotypic plasticity reduces lag phases in situations where hazards threaten specimens over several generations. We tested this in three generations of the freshwater crustacean Daphnia lumholtzi using the three-spined stickleback Gasterosteus aculeatus as predator. In the presence of chemical cues from fish D. lumholtzi expresses elongated head and tail spines. In the F0 generation defenses are constraint by a comparatively long lag phase and are not developed prior to the 3rd instar. In the F1, and F2 of induced animals this lag phase is shortened and defenses are developed upon birth. We show that induction of TGP in the mothers takes place already during the juvenile stages and transfers to the offspring generation in forms of shortened time lags and enhanced trait expression. When progeny is additionally exposed to fish cues as embryos, the addition of maternal and embryonic effects further enhances the magnitude of defense expression. Our findings detail a distinguished strategy of transgenerational phenotypic plasticity which allows to shorten lag phases of trait changes in phenotypic plasticity.